2018
DOI: 10.1007/s12016-018-8708-x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Avoidance: the Psychosocial Impact of Food Allergies

Abstract: Over the past few years, the rates of food allergies have dramatically increased. As a result, the lives of patients and their caregivers have been dramatically altered. While most attention surrounding food allergies has focused on treatment, less consideration has been given to the mental health ramifications of living with this condition, among them depression, anxiety, post-traumatic stress, being bullied, and an overall poorer quality of life. At the same time, patients' family lives are often disrupted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 51 publications
0
73
0
5
Order By: Relevance
“…[1][2][3][4][5][6] The traditional approach in food-allergic patients, consisting of an elimination diet, is hampered by adverse reactions due to accidental exposures and is associated with significantly impaired quality of life (QOL). [7][8][9][10][11] Oral immunotherapy (OIT) has been shown to be an effective alternative treatment for patients with food allergy [12][13][14][15][16][17][18][19][20][21][22][23] and was recently recommended as a treatment option by the European Academy for Allergy and Clinical Immunology. 20 However, the treatment itself imposes many difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The traditional approach in food-allergic patients, consisting of an elimination diet, is hampered by adverse reactions due to accidental exposures and is associated with significantly impaired quality of life (QOL). [7][8][9][10][11] Oral immunotherapy (OIT) has been shown to be an effective alternative treatment for patients with food allergy [12][13][14][15][16][17][18][19][20][21][22][23] and was recently recommended as a treatment option by the European Academy for Allergy and Clinical Immunology. 20 However, the treatment itself imposes many difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the physical consequences of an allergic reaction, a multitude of adverse psychosocial aspects of living with FA exist, such as anxiety, social isolation, and related bullying. 10,11 The approval by the US Food and Drug Administration (FDA) of Palforzia in January 2020, the first drug approved for FA in the form of peanut oral immunotherapy (OIT), 12 is a first step towards safe and effective treatments for FA. Palforzia is a highly characterized and standardized peanut OIT formulation.…”
Section: Introductionmentioning
confidence: 99%
“…18.0% of parents in this study reported high FAAA. Although there was no control group in this study, others have found higher anxiety in parents of food‐allergic children compared with controls 16 . Compared with mean STAI‐S scores from studies of mothers of patients enrolled from paediatric allergy clinics, the mean STAI‐S score for parents in this study (42.0) was higher than that reported in three studies in the United Kingdom (34.6, 36.2, 38.0), 7,17,18 and similar to a Turkish study (41.5) 19 .…”
Section: Discussionmentioning
confidence: 74%
“…In addition, sensitivity and specificity analysis, and factor analysis, from this study points to a common theme that current available measures (eg STAI, FAQL‐PB), while frequently used in food allergy research, do not adequately identify parents who are highly anxious about their child's food allergy. Given that excessive anxiety in parents of children with chronic disease can have negative consequences on the parent and the child, 16 it is important to develop a validated FAAA screening tool for use outside of research that can be completed quickly by parents and interpreted easily by allergists. Building upon these results, future research by the authors of this study will include development of a validated FAAA screening tool for the clinical setting, to identify parents with high FAAA so that psychosocial supports and resources (which are limited in many settings) can be targeted towards those who most need them.…”
Section: Discussionmentioning
confidence: 99%